Premium Reserves Calculation on Whole Life Insurance Using The Fackler Method - Jabbarudin, Akbar; Sudding, Fauziah Nur Fahirah (Journal of Actuarial, Finance, and Risk Management, 2025)
Everyone has a risk of death and as they get older, the risk of death will increase. Therefore, everyone suggested to have insurance. Not only for individual, the risk is also faced with insurance provider. There are several categories of life insurance. One of the category is whole life insurance. Whole life insurance has benefitfor lifetime of the insured. The insurance provider will pay beneficiaries when the policyholder dies within any years. There are two major methods of calculating premium reserve which are prospective and retrospective method. The Fackler method adapting the concept of retrospective method. The assumptions of the Fackler method that final reserve value is determined as the reserve at the end of the next year. Considering the long-term impact, this study conducted premium reserves calculation on whole life insurance using the Fackler method. This study use “Tabel Mortalitas Penduduk Indonesia 2023” from BPJS Kesehatan as Mortality Data and 5.75% as interest rate from BI-Rate. The result of this study shows that the amount of premium reserves reaches the promised benefit at the age of 67 years old for male and 70 years old for female. Life expectancy in Indonesia is 73 years old for male and 78 years old for female. Based on the result, the Fackler method success reaches the promised benefit below life expectancy Indonesia.